Expansile cribriform Gleason pattern 4 has histopathologic and molecular features of aggressiveness and greater risk of biochemical failure compared to glomerulation Gleason pattern 4. Issue 8 (27th March 2020) - Greenland, Nancy Y.; Cowan, Janet E.; Zhang, Li; Carroll, Peter R.; Chan, Emily; Stohr, Bradley A.; Simko, Jeffry P.
Abstract: Background: Molecular testing of prostate cancer biopsies with Gleason pattern 4 suggests the expansile cribriform pattern is more aggressive than the glomerulation pattern. These two extreme patterns have not been compared at prostatectomy. We hypothesized that at prostatectomy the expansile cribriform pattern would be associated with histopathologic and molecular features of aggressiveness and with greater risk of biochemical recurrence (BCR) than the glomerulation pattern. Methods: In a retrospective cohort study, radical prostatectomy reports with expansile cribriform pattern or glomerulation pattern were analyzed for percentage of total pattern 4, extraprostatic extension (EPE), positive lymph nodes, seminal vesicle invasion (SVI), and intraductal carcinoma (IDC). Cases with pattern 5 or with both expansile cribriform and glomerulations patterns present were excluded. The electronic medical record was reviewed for BCR‐free survival and for Decipher test results. Results: Of 1020 radical prostatectomies from July 2015 to July 2018, 110 (11%) had either expansile cribriform or glomerulation pattern present. The expansile cribriform group was associated with more histopathologic features of aggressiveness, with higher average total percentage pattern 4 (43.7 vs 27.0, P = .002), a trend of greater extensive EPE (32.7% vs 17.2%, P = .06), a trend toward statistical significance of higher rate of SVI (11.5% vs 3.4%, P = .1), greater positive lymph nodes (9.6% vs 0%, P = .02), and a higher percentage of cases with or suspicious for IDC (23.1% vs 8.6%, P = .04). The risk of BCR was 4.4 (1.3‐15.4) fold greater for the expansile cribriform group vs the glomerulations group ( P = .02). For the 38 patients who underwent Decipher testing, the expansile cribriform group had a high‐risk assay category mean score whereas the glomerulations group had an average risk assay category mean score (0.61 vs 0.47, P = .02). Conclusions: In a comparison of prostatectomy cases with expansile cribriform pattern to those with glomerulation pattern, the expansile cribriform pattern was associated with more histopathologic features of aggressiveness, greater risk of biochemical failure, and higher scores with a molecular classifier (Decipher) test. These findings underscore the importance of reporting the types of pattern 4 and supports the argument that men with expansile cribriform likely require more aggressive management.